History of Spinal Cord “Pain” Pathways Including the Pathways Not Taken - Basbaum, Allan (Frontiers in Pain Research, 2022)
Traditional medical neuroanatomy/neurobiology textbooks teach that pain is generated by several ascending pathways that course in the anterolateral quadrant of the spinal cord, including the spinothalamic, spinoreticular and spinoparabrachial tracts. The textbooks also teach, building upon the mid-19th century report of Brown-Séquard, that unilateral cordotomy, namely section of the anterolateral quadrant, leads to contralateral loss of pain (and temperature). In many respects, however, this simple relationship has not held up. Most importantly, pain almost always returns after cordotomy, indicating that activation of these so-called “pain” pathways may be sufficient to generate pain, but they are not necessary. Indeed, Brown-Séquard, based on his own studies, eventually came to the same conclusion. But his new view of “pain” pathways was largely ignored, and certainly did not forestall Spiller and Martin's 1912 introduction of cordotomy to treat patients. This manuscript reviews the history of “pain” pathways that followed from the first description of the Brown-Séquard Syndrome and concludes with a discussion of multisynaptic spinal cord ascending circuits. The latter, in addition to the traditional oligosynaptic “pain” pathways, may be critical to the transmission of “pain” messages, not only in the intact spinal cord but also particularly after injury.